Tuberculosis infection control knowledge and attitudes among health workers in Uganda: a cross-sectional study - Buregyeya, Esther (BMC Infect Dis, 2016)
BACKGROUND: The World Health Organization recommends TB infection control (TBIC) in health care facilities. In 2008, the Ministry of Health Uganda initiated efforts to implement TBIC by training of health care workers (HCWs). This study was carried out to assess knowledge and attitudes towards TBIC among HCWs. METHODS: We conducted a cross-sectional study among HCWs in health facilities in the districts of Mukono and Wakiso in Uganda, from October 2010 to February 2011. We assessed HCWs’ knowledge of basic standards of TB diagnosis, treatment and TBIC and attitudes towards TBIC measures. RESULTS: Twenty four percent of the participants answered correctly all the basic TB knowledge questions. Overall, 62 % of the HCWs were judged to have adequate basic TB knowledge. At multivariable analysis, non-clinical cadres, were more likely to have poor basic TB knowledge, [adjusted odds ratio (aOR) 0.43; 95 % confidence interval (CI) 0.27–0.68)]. Only 7 % of the respondents answered all the questions on TBIC correctly. Almost all the respondents (98 %; 529/541) knew that TB was transmitted through droplet nuclei, while only a third (34 %; 174/532) knew that masks do not protect the wearer from getting TB. Overall, 69 % (355/512) of the HCWs were judged to have adequate TBIC knowledge. At multivariable analysis, non-clinical cadres (aOR 0.61; 95 % CI 0.38–0.98) and having not attended TBIC training, (aOR 0.65; 95 % CI 0.42–0.99), were more likely to have poor TBIC knowledge. More than three quarters (77 %; 410/530) and 63 % (329/522) of the respondents had a high self-efficacy and perceived threat of acquiring TB at work, respectively. Having not attended a TBIC training was significantly associated with a low self-efficacy (aOR 0.52; 95 % CI 0.33–0.81) and low perceived threat of acquiring TB infection at work, (aOR 0.54; 95 % CI 0.36–0.81). CONCLUSIONS: Our study finds moderate number of HCWs with correct knowledge and attitudes towards TBIC. Efforts should be put in place to train all HCWs in TBIC, with particular emphasis on the non-clinical staff due to their limited grasp of TBIC measures.